English in the lower grades of the public schools - Reynolds, Jessie A. (My University, 1906)
Introduction: It is now generally conceded by our later and best grammarians that comparatively little so-called grammar should be taught below the high school; and I am sure that those of us who are struggling with the problems in English in much humbler positions quite agree. With that as a premise then, I dismiss the subject of technical grammar and take up for the grades only what has come to be known as the language or the mans for effective expression, leaving the corrective element subordinate. The problem before us is not an easy one. In the beginning we note many difficulties confronting the primary teacher. She has usually a large room overcrowded with little ones, coming from different homes, from different surroundings and with the consequently widely varying vocabularies. Yet by our present school system she must take all these many minds, put them all through the same machine-like training and turn them out at last all equally complete. The child coms to the primary teacher from an environment where he is used to asking the whys and wherefores of everything; where the anxious mother and interested father have been happy over all his conversations. Such a condition has made him wonderfully self-centered, but has given him a fondness for conversation, and for the narration of personal experiences that if used properly, form the very best basis for our work. He has a small horizon, but one capable of infinite expansion.
Citation: Reynolds, Jessie A. English in the lower grades of the public schools. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: English Language; Public Schools; Grade School; Theses; Manuscripts (documents)